Book reviews: “Julian Havil; Curves for the Mathematically Curious: An Anthology of the Unpredictable, Historical, Beautiful, and Romantic”, Princeton University Press, 2019, xviii+280 p. ISBN 978-0-691-18005-2/hbk; 978-0-691-19778-4/ebook. - COBZAȘ, S. (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
The book contains ten chapters, each one describing a famous curve: 1. The Euler curves; 2. The Weierstrass curve; 3. B´ezier curves; 4. The rectangular hyperbola; 5. The quadratrix of Hippias; 6. The space filling curves; 7. Curves of constant width; 8. The normal curve; 9. The catenary, and 10. Elliptic curves.